Incidence and maternal-perinatal outcomes of uterine rupture in a university hospital in Eastern Ethiopia: A retrospective study - Abebe, Fiseha; Eticha, Tadesse Gure; Belis, Bikila; Tura, Abera Kenay (Ethiopian Journal of Reproductive Health, 2025)
Abstract Background: Uterine rupture remains a major public health problem in many low-resource settings, such as Ethiopia. Understanding the incidence and maternal and perinatal outcomes of uterine rupture is essential for designing appropriate interventions. Objective: This study was conducted to assess the incidence, trends, and maternal and perinatal outcomes of uterine rupture among women who gave birth at a university hospital in Eastern Ethiopia over a five-year period. Methods: A facility-based retrospective study was conducted from October 1–31, 2023, among all women who gave birth from January 1, 2018, to December 31, 2022, at Hiwot Fana Comprehensive Specialized University Hospital. For the maternal and perinatal outcomes, we considered onlyuterine rupture cases. A pretested checklist was used to collect the data through a review of the medical records of the woman. The collected data were coded, cleaned, entered into EpiData 4.6 and exported to SPSS 26 for analysis. We described the findings via tables and figures. Results: Of a total of 24,608 births during the study period, 168 had uterine rupture, corresponding to an incidence rate of 6.8 per 1000 births. There was no significant change in the trend of uterine rupture over the five years of the study period. Among the 153 cases of uterine rupture for which complete information was available, 119 (90.8%) stillbirths, 113 (73.9%) severe hemorrhages, 79 (51.6%) hysterectomies, 13 (8.5%) bladder ruptures, 9 (5.5%) obstetric fistulas, and 5 (3.3%) maternal deaths occurred. Conclusion: Although the incidence of uterine rupture is low, it is associated with high rates of adverse maternal and perinatal outcomes. An audit of the timeliness and appropriateness of the care provided is essential for preventing the associated high adverse maternal and perinatal outcomes.